Towards high-precision IMU/GPS-based stride -parameter determination in an outdoor runners` scenario - Bichler, S.; Ogris, G.; Kremser, V.; Schwab, F.; Knott, S.; Baca, A. (Procedia Engineering, 2012)
Movement variability has received great attention due to evidence of its functional meaning, and thus offers potential for training optimization. The study on hand presents an extended pedestrian-dead-reckoning approach to stride parameter estimation in running on an athlete track. In addition, the supposed measurement system is evaluated by means of a video-based reference system. This pilot study revealed that the proposed approach promises to be successful for high accuracy stride parameter estimation.